PENGOLAHAN LIMBAH PLASTIK MENJADI PRODUK KERAJINAN TANGAN UNTUK MENINGKATKAN EKONOMI MASYARAKAT SENDANG DAJAH (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2020)
This research is a form of research that is devoted to the realiasasi community. Research this time raised the issue of the handling of plastic waste which can give added value to be hand- crafted. The object of the research is done at the village, district of Dajah Sendang Madura, Indonesia. Research conducted with observational approach to the issue and allotment of intervention against the problems raised. In more detail, the plasik waste management approaches in interventions is the plastic wrap from drinks powder. The method of intervention is done by providing training to women in the area of the village of Dajah Sendang which profession as a member of the family prosperity coaching (PKK). Approach to interventions made during the six-week period in mid-November to late December 2018. The result of this activity is the formation of creative products in the form of bags that have a value and can sell the public consumption. Training done dap.